INTERACTIVE METADISCOURSE IN GUARDIAN AUSTRALIA’S TIKTOK AND WEBSITE NEWS REPORTS - Munawaroh, Paridotul; Ishlahiyah, Mazroatul (Annual International Conferences on Language, Literature, and Media, 2023)
This qualitative research aimed to analyze and compare the various types of interactive metadiscourse markers in the spoken news and written news stories of Guardian Australia. The researchers selected Guardian Australia as the focus due to its utilization of the TikTok media platform, which has experienced significant growth in recent years, to disseminate news content. Besides determining the types of interactive metadiscourse employed in both spoken and written news reports in Guardian Australia, the study also identifies the similarities and differences in using interactive metadiscourse across the two mediums. The data were in words, phrases, and sentences encompassing interactive metadiscourse employed inside the spoken and written news reports of Guardian Australia using Hyland's theory (2005). The researchers discovered 66 data points, comprising 34 spoken and 32 written news reports. The spoken news report consists of 14 instances of transition data, 11 instances of frame markers data, 5 instances of evidentiary data, and 4 instances of code glosses data. In the written news story, the data analysis revealed the presence of transition 13 data, endophoric markers 1 data, evidential 13 data, and code glosses 5 data. The findings indicated that interactive metadiscourse in spoken news may be categorized into four types: transition, frame markers, evidential, and code glosses, while written news exhibits four types of interactive metadiscourse: transition, endophoric, evidential, and code glosses.